PS2-6: Using Health Risk Assessments to Understand Older Adult Sedentary Time - Rosenberg, Dori (Clin Med Res, 2014)
BACKGROUND/AIMS: Sedentary time (ST) is independently associated with cardio-metabolic conditions and mortality. Older adults have the highest levels of ST of all age groups. Little is known about how ST relates to BMI, health conditions, and health costs in older adults. Our aim was to use electronic health records (EHR) to better explore these relationships. METHODS: We extracted health risk assessment data (HRA), outpatient visit diagnosis codes, and total healthcare costs from the EHR of a large health plan in WA State (Group Health). All members aged 65–99 who completed an HRA in 2011 and were continuously enrolled for 2 years, did not reside in long-term care, or have a terminal health condition were included (N = 3967; ~10% of all eligible members). ST was assessed by the International Physical Activity (PA) Questionnaire sitting item. BMI was calculated using most recent weight and height from the EHR. Cardiovascular disease and diabetes were identified using ICD-9 codes. We used regression analysis to determine how mean ST varied with factors such as diabetes, while controlling for age, gender, race, ethnicity, BMI, diet, and hours of PA per week. RESULTS: Age and PA were strongly related to ST. Obese participants (BMI >30 (24% of the sample) had significantly higher mean ST (6.75 hours/day, P <.001) compared to overweight (6.06) and normal weight (5.67) older adults. Those with diabetes (14% of the sample), had significantly higher ST (6.42 hours/day) than those without (6 hours/day; P = .01). Total healthcare costs increase on average $139 for each additional hour of sitting (P = .03). CONCLUSIONS: After adjusting for demographic, health behaviors, and health conditions, older adults with a higher BMI, diabetes, and higher total healthcare costs had greater self-reported ST. These patterns indicate that ST may be an important health behavior to target for intervention as people age.